Adequacy of measures of informed consent in medical practice: A systematic review. - Kerry A Sherman (Public Library of Science (PLoS), 2021)
As a critical component of medical practice, it is alarming that patient informed consent does not always reflect (1) adequate information provision, (2) comprehension of provided information, and (3) a voluntary decision. Consequences of poor informed consent include low patient satisfaction, compromised treatment adherence, and litigation against medical practitioners. To ensure a well-informed, well-comprehended, and voluntary consent process, the objective and replicable measurement of these domains via psychometrically sound self-report measures is critical. This systematic review aimed to evaluate the adequacy of existing measures in terms of the extent to which they assess the three domains of informed consent, are psychometrically sound and acceptable for use by patients. Extensive searching of multiple databases (PsychINFO, PubMed, Sociological Abstracts, CINAHL, AMED) yielded 10,000 potential studies, with 16 relevant scales identified. No existing scale was found to measure all three consent domains, with most only narrowly assessing aspects of any one domain. Information provision was the most frequently assessed domain, followed by comprehension, and then voluntariness. None of the identified scales were found to have adequate evidence for either high quality psychometric properties or patient user acceptability. No existing scale is fit for purpose in comprehensively assessing all domains of informed consent. In the absence of any existing measure meeting the necessary criteria relating to information, comprehension and voluntariness, there is an urgent need for a new measure of medical consent to be developed that is psychometrically sound, spans all three domains and is acceptable to patients and clinicians alike. These findings provide the impetus and justification for the redesign of the informed consent process, with the aim to provide a robust, reliable and replicable process that will in turn improve the quality of the patient experience and care provided.